Fin whales and microplastics: The Mediterranean Sea and the Sea of Cortez scenarios. (February 2016) - Fossi, Maria Cristina; Marsili, Letizia; Baini, Matteo; Giannetti, Matteo; Coppola, Daniele; Guerranti, Cristiana; Caliani, Ilaria; Minutoli, Roberta; Lauriano, Giancarlo; Finoia, Maria Grazia; Rubegni, Fabrizio; Panigada, Simone; et al.
Abstract: The impact that microplastics have on baleen whales is a question that remains largely unexplored. This study examined the interaction between free-ranging fin whales ( Balaenoptera physalus ) and microplastics by comparing populations living in two semi-enclosed basins, the Mediterranean Sea and the Sea of Cortez (Gulf of California, Mexico). The results indicate that a considerable abundance of microplastics and plastic additives exists in the neustonic samples from Pelagos Sanctuary of the Mediterranean Sea, and that pelagic areas containing high densities of microplastics overlap with whale feeding grounds, suggesting that whales are exposed to microplastics during foraging; this was confirmed by the observation of a temporal increase in toxicological stress in whales. Given the abundance of microplastics in the Mediterranean environment, along with the high concentrations of Persistent Bioaccumulative and Toxic (PBT) chemicals, plastic additives and biomarker responses detected in the biopsies of Mediterranean whales as compared to those in whales inhabiting the Sea of Cortez, we believe that exposure to microplastics because of direct ingestion and consumption of contaminated prey poses a major threat to the health of fin whales in the Mediterranean Sea. Graphical abstract: Highlights: Microplastics and phthalates were higher in the Mediterranean Sea than in the Sea of Cortez. The overlap between the whale feeding areas and high microplastic density shows the risk of interaction. Data suggest an increasing risk of chemical transfer from microplastic to whales during the foraging. Mediterranean whales are exposed to higher ecotoxicological threat of than Sea of Cortez whales. Abstract : This study identified temporal and regional ecotoxicological variations in free-ranging fin whales inhabiting two seas different characterized by different microplastic abundance.